Recovery of Motor Function Following Spinal Cord Injury - Fuller, Heidi; Gates, Monte (IntechOpen, 2016)
Restoration of motor function following spinal cord injury is a complex and challenging task. By reviewing emerging cellular, pharmacological, rehabilitative, as well as surgical approaches, this book seeks to highlight promising therapeutic strategies for the repair and regeneration of motor circuitry. The multidisciplinary nature of these approaches illustrates various routes to bridging the gap between the bench and the bedside and to identify the challenges that must be overcome in order to bring about a viable therapeutic strategy for spinal cord injury patients.